Quality Management and Market Orientation Affecting the Organizational Performance of SMEs in Thailand - Kanthachai, Nongnout (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research aimed to study (1) the levels of quality management, market orientation, and organizational performance, (2) the levels of environmental uncertainty, and (3) the quality management and market orientation that affect the organizational performance of small and medium-sized enterprises (SMEs). The sample size was 1,200 entrepreneurs and the data were analyzed by computer program. The findings found that most respondents were male, aged between 41-50 years old with a bachelor’s degree or equivalent, and a retail enterprise with an investment of 5-10 million baht with 25-49 workers. In general, the quality level of management was quite high with the highest mean for products and services’ design. The market orientation displayed a high level of mean with the highest score for customer responsibility. The operational performance showed a rather high mean with the highest score found in quality of results. The environmental uncertainty also registered quite a high mean with the highest score for customer. Importantly, the Structural Equation Model (SEM) was applied to investigate the two factors of quality management and market orientation that affect the operational performance of SMEs. The basic statistic results indicated that this model was correlated with its collected data. Moreover, the quality management had a direct effect on the market orientation, and the market orientation had a direct effect on the operational performance.